The Effect of Realistic Mathematics Education on the Mathematical Problem-Solving Ability of Fifth-Grade Students at SD 21 Banda Aceh - Hayati, Zikra; Razia, Indah; Yacob, Fakhri (Jurnal keilmuan dan Kependidikan dasar, 2026)
This research to examine the effect of implementing the Realistic Mathematics Education (RME) model on students' mathematical problem-solving abilities. This research employs a quantitative approach with a quasi-experimental design, specifically a control group pretest–posttest design. The sampling technique used is random sampling. The population of this study consisted of fifth-grade students, while the sample consisted of two groups: an experimental group consisting of 17 students taught using the RME model, and a control group consisting of 17 students taught using conventional instruction. Data were collected using a mathematical problem-solving ability test. Data analysis was conducted using an independent sample t-test with the assistance of SPSS version 26 for Windows. The results indicate a significant difference between the group that received the RME treatment and the group that received conventional instruction, with a significance value of 0.003 < 0.05. This finding demonstrates that the implementation of the RME model has a significant effect on improving students' mathematical problem-solving abilities. Therefore, the RME model can serve as an effective alternative instructional approach to enhance problem-solving skills among elementary school students.